Problems of Children’s Education on the Coast - Putri, Viona Yolanda; Nursaimah, Nursaimah; Farhan, Muhammad; Zen, Auliya Rahmi (International Journal of Multidisciplinary Research of Higher Education, 2021)
Education is one of the main keys to creating and forming Indonesian human qualities that are superior and have strong competitiveness. In Indonesia, children's education on the coast generally has the same problems, namely low levels of education and inadequate socio-economic life. Thus this study aims to analyze what are the problems of children's education on the coast. This research uses a qualitative method with an approach to ethnography. The research data was taken from eight informants consisting of children, parents, and the surrounding community. To strengthen the interview data the authors also made direct observations of children in coastal areas. Interview and observation data were analyzed using Analysis Interactive Model Milles & Hubberman. The results of this study are that there are five problems that hinder children's education on the coast, namely inadequate economic conditions, children's desire to follow their parents' career path, low interest in learning in children, lack of motivation from parents to go to school and environmental factors and friends. The results of this study can be used as information for the community to find solutions to existing problems.